ANALISIS RISIKO PRODUKSI CABAI BESAR DI KECAMATAN SIKUR KABUPATEN LOMBOK TIMUR - Putri, Silvia Devi Kharisma; Amiruddin, Amiruddin; Usman, Abdullah (AGROTEKSOS; Vol 31 No 1 (2021): Jurnal Agroteksos April 2021DO - 10.29303/agroteksos.v31i1.587, 2022)
This study aims to: (1) determine the production of large chili farming in Sikur Subdistrict, East Lombok Regency; (2) analyzing production risk in large chili farming in Sikur District, East Lombok Regency; (3) analyzing the factors that affect production risk in large chilli farming in Sikur District, East Lombok Regency; (4) determine recommendations for handling production risks in large chili farming in Sikur District, East Lombok Regency. This research uses a descriptive method. Determination of the sample area is done by puposive sampling method. The number of respondents was determined by a quota sampling of 40 chilli farmers. The results showed that: (1) The average large chili production was 12,245 kg / ha; (2) The risk of large chili production is relatively high with a coefficient of variation (CV) of 0.51; (3) Factors that increase the risk of positive production or opportunity are manure, growth regulators, and irrigation intensity. Whereas seeds, chemical fertilizers, and the intensity of HPT attacks are factors that reduce the risk of positive production or opportunity. Factors that increase the risk of negative production are chemical fertilizers, irrigation intensity, and pest plant disease attack intensity. Whereas seeds, manure, and growth regulators are factors that reduce the risk of negative production. Recommendations for handling production risks to increase the risk of positive production (opportunity), namely by reducing the amount of use of seeds, chemical fertilizers, increasing the amount of use of manure, growth regulators, irrigation intensity, and controlling pest plant disease properly. Whereas recommendations to reduce the risk of negative production are to increase the amount of use of seeds, manure, growth regulators, reduce the amount of use of chemical fertilizers, irrigation intensity, and control pest plant disease properly.